Progressive Region-Specific De Novo Methylation of the p16 CpG Island in Primary Human Mammary Epithelial Cell Strains during Escape from M(0) Growth Arrest - Wong, David J. (American Society for Microbiology, 1999)
CpG island methylation plays an important role in normal cellular processes, such as genomic imprinting and X-chromosome inactivation, as well as in abnormal processes, such as neoplasia. However, the dynamics of de novo CpG island methylation, during which a CpG island is converted from an unmethylated, active state to a densely methylated, inactive state, are largely unknown. It is unclear whether the development of de novo CpG island methylation is a progressive process, in which a subset of CpG sites are initially methylated with a subsequent increase in methylation density, or a single event, in which the initial methylation event encompasses the entire CpG island. The tumor suppressor gene p16/CDKN2a/INK4a (p16) is inactivated by CpG island methylation during neoplastic progression in a variety of human cancers. We investigated the development of methylation in the p16 CpG island in primary human mammary epithelial cell strains during escape from mortality stage 0 (M(0)) growth arrest. The methylation status of 47 CpG sites in the p16 CpG island on individual DNA molecules was determined by sequencing PCR clones of bisulfite-treated genomic DNA. The p16 CpG island was initially methylated at a subset of sites in three discrete regions in association with p16 transcriptional repression and escape from M(0) growth arrest. With continued passage, methylation gradually increased in density and methylation expanded to sites in adjacent regions. Thus, de novo methylation in the p16 CpG island is a progressive process that is neither site specific nor completely random but instead is region specific. Our results suggest that early detection of methylation in the CpG island of the p16 gene will require methylation analysis of the three regions and that the identification of region-specific methylation patterns in other genes may be essential for an accurate assessment of methylation-mediated transcriptional silencing.